Child victims and female perpetrators: dealing with the Nazi-murder of disabled children in the postwar Soviet Union - Penter, Tanja (Ukraïna moderna, 2020)
Using postwar trial materials from Ukrainian former KGB archives, the paper examines the Nazi-murder of disabled patients under German occupation in Ukraine (1941-43). In two mass murder operations, 144 disabled children were shot by different German perpetrators in October 1941 and in March 1943 at a colony for disabled children in Preslav, Zaporizhia region. This crime is indicative of a multitude of similar crimes against disabled and sick patients in the territory of the occupied Soviet Union. For this crime in Preslav (as well as for many similar crimes in Ukraine) no German perpetrators have ever been brought to trial until today. But postwar Soviet investigations of the case resulted in seven Soviet former employees of the colony - among them four women (doctors and members of the nursing staff) - being put on trial and convicted for complicity with the Germans in the crime.
Gesehen am 26.01.2026
DOI fehlerhaft